2014
DOI: 10.1080/17451000.2014.928414
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective evaluation of the Barents Sea capelin management advice

Abstract: Since 1998, the assessment model framework Bifrost/Captool has been used for advice on total allowable catch for the Barents Sea capelin (Mallotus villosus) stock. However, since the management is based on a target escapement strategy, and most capelin die after spawning, viewed in retrospect, there is hardly any possibility of checking whether the forecast underpinning the quota was actually realistic. The forecast using Captool for the period from 1 October up to capelin spawning time at 1 April relies on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…In the Barents Sea, cod consumption of capelin has been implemented in short‐term predictions of capelin stock biomass since the 1990s (Gjøsæter et al . ). Retrospective analyses performed by Gjøsæter et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the Barents Sea, cod consumption of capelin has been implemented in short‐term predictions of capelin stock biomass since the 1990s (Gjøsæter et al . ). Retrospective analyses performed by Gjøsæter et al .…”
Section: Discussionmentioning
confidence: 97%
“…Retrospective analyses performed by Gjøsæter et al . () demonstrated that the cod stock predictions used for estimating consumption were consistently too small. This bias has resulted in predictions of too large capelin stocks and therefore the setting of larger quotas than prescribed by the agreed HCR.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, coverage of the benthic part of the ecosystem has become much better. This knowledge has yielded many scientific papers that would otherwise not have been possible (Gjøsaeter et al, 2009(Gjøsaeter et al, , 2015Fossheim et al, 2015;Jørgensen et al, 2015;Johannesen et al, 2012aJohannesen et al, , 2012bHaug et al, 2017;Kjesbu et al, 2014). However, the broadening of the data collection comes at a cost related to increased survey time and decreased spatial resolution compared to the specialized surveys that formed the basis for the BESS.…”
Section: Discussionmentioning
confidence: 99%
“…Norway has taken a number of steps to implement an ecosystem-based management scheme for the Barents Sea (Olsen et al, 2007). For example, Barents Sea capelin stock assessment scientists have for a number of years estimated cod predation (Gjøsaeter et al, 2015) and has developed at least the scientific basis for including the cod-capelin interaction in cod management. Given that capelin and cod are, typically, harvested by different fishing vessels and that Russia and Norway may value these stocks differently, it would require substantial political will to include the cod-capelin interaction in the HCR.…”
Section: Northeast Arctic Codmentioning
confidence: 99%
“…Recently, a new harvest control rule was introduced, again modelled after the harvest control rule for the Barents Sea capelin (Gjøsaeter et al, 2015), where empirical uncertainty is taken into account. The new rule also reflects predation on capelin that takes place between the time of the acoustic measurements of the spawning migration and the spawning season.…”
Section: Icelandic Capelinmentioning
confidence: 99%